THE TRANSLATABILITY OF COMPOUND WORDS IN THE HUNGER GAMES IN ENGLISH AND INDONESIAN - Dwi Apcita Estorina; Ikmi Nur Oktavianti (Universitas Ahmad Dahlan)
English is used as a foreign language in some countries since it is one of international languages. In Indonesia, English is not the mother tongue of the majority of occupants, so the translation is needed to solve the communication problem between two different languages. This research entitled “The Translatability of Compound Words in The Hunger Games in English and Indonesian Versions” is intended to find out the English compound words equivalently translatable into Indonesian found in the novel and to describe the causes of the non-equivalent translation.This research belongs to descriptive qualitative research as the research design. The research object of this research is compound and the data of this research is the compound words of English language and Indonesian language. As for the data source, The Hunger Games novel is used as the data source of the research. In collecting the data, the researcher uses observing method. In observing method, the researcher reads, underlines, and transcribes the compound words of English and Indonesian language found in the novel. In data analysis, the researcher identifies the data based on English language and Indonesian language compound words.The analysis of the research shows that there are English compound words that can be equivalently translatable into Indonesian and some cannot. The non-equivalent translation of the compounds has the highest frequency that is 29 cases. It happens because the translator translated the English compound words into words and phrases. The frequency of equivalent translation is 21 cases in which the translator translated the English compound words into Indonesian compound. As for the causes, there are some factors triggering the inability to translate equivalently and one of the most influencing ones is cultural aspect.